pemdas
you ALWAYS have to so the operations from left to right
P: parentheses
E: exponents
M: multiplication (either or)
D: division
A: addition (either or) from the
S: subtract
Your equation: 8^2+3(36÷6)-2
You do parentheses first which is 36÷6=6
So now you have 8^2+3(6)-2
Now you do exponents which is 8^2=64
So now you have 64+3(6)-2
After you MULTIPLY, so you will NEVER have 67 as an answer.
So you multiply 3(6)=18
And now your new equation is (64+18)-2
64+18=82
And now you have 82-2=80
And that is your answer.